ETS Proto-Oncogene 1 Suppresses MicroRNA-128 Transcription to Promote Osteogenic Differentiation Through the HOXA13/β-Catenin Axis - Li, Renyao; Dong, Ying; Li, Feipeng (Frontiers in Physiology, 2021)
ETS proto-oncogene 1 (ETS1) has been implicated in osteoporosis (OP), but the exact molecular mechanisms are complex. This work focuses on the impact of ETS1 on the osteogenic differentiation and the molecules involved. A mouse pre-osteoblast cell line MC3T3-E1 was used for in vitro experiments. ETS1 was upregulated during the process of osteogenic differentiation of MC3T3-E1 cells. Overexpression of ETS1 promoted expression of osteogenic markers, alkaline phosphate concentration, and calcareous accumulation in cells. ETS1 was found to specifically bind to miR-128 promoter to suppress its transcription, while miR-128 could target homeobox A13 (HOXA13). Therefore, ETS1 suppressed miR-128 transcription to upregulate HOXA13 expression. Overexpression of HOXA13 promoted the osteogenic differentiation ability of cells and increased the protein level of β-catenin. Either overexpression of miR-128 or downregulation of β-catenin by CWP232228, a β-catenin-specific antagonist, blocked the promoting roles of ETS1 in cells. To conclude, this study provided evidence that ETS1 suppresses miR-128 transcription to activate the following HOXA13/β-catenin axis, therefore promoting osteogenic differentiation ability of MC3T3-E1. This finding may offer novel ideas for OP treatment.